Evaluation of an integrated care program for thoracic surgery in Ontario, Canada: a historical cohort study - Nicholas Bakewell; Catherine Liang; Tsoleen Ayanian; Sanjana Sundaram; Kazuhiro Yasufuku; Meghan O’Neill; Kathy Kornas; Lori Diemert; Megan Samantha Lowe; Melissa Chang; Laura C. Rosella (BMC Health Services Research)
Abstract Introduction Integrated care (IC) may help to improve postoperative health outcomes among thoracic surgery patients. We conducted an outcome evaluation of an IC program implemented within the Division of Thoracic Surgery of a large hospital network in Ontario, Canada. Methods Historical cohort design using data on patients who underwent thoracic surgery to compare outcomes of two IC groups (Pre-COVID IC: June 2019-February 2020; COVID IC: March 2020-September 2022), to a Historical non-IC group (June 2018-February 2019). Stratified by care path (low [minimally invasive procedures], medium [other procedures], high [complex procedures]), we compared risks of readmissions and emergency department (ED) visits, and mean length of stay (LOS) and healthcare costs up to 90 days post-discharge using modified Poisson/Ordinary Least Squares, Negative Binomial and Gamma regression, respectively, adjusting for age, sex, and location of residence. Results In total, 1572 patients were included (Pre-COVID IC (n = 269); COVID IC (n = 869); Historical non-IC (n = 434)), with the largest proportion enrolled in the low care path. Compared to the Historical non-IC group, both the Pre-COVID and COVID IC groups had a statistically significantly shorter mean index LOS in the low (relative mean difference (RMD): 0.74 (95% confidence interval: 0.63–0.88) [Pre-COVID]; 0.66 (0.58–0.75) [COVID]) and medium (RMD: 0.75 (0.59–0.97) [Pre-COVID]; 0.62 (0.51–0.74) [COVID]) care paths; results were similar for total LOS (including readmissions). In contrast, the Pre-COVID IC group had a statistically significantly higher mean index LOS in the high care path (RMD: 1.39 (1.02–1.89)). The Pre-COVID IC group had a statistically significantly lower risk of 90-day ED visits in the low care path (relative risk (RR): 0.59 (0.36–0.97)) and a statistically significantly lower mean index cost in the medium care path (RMD: 0.72 (0.52–0.99)). The COVID IC group had a statistically significantly lower risk of 90-day readmissions in the low care path (RR: 0.64 (0.42–0.97)). Conclusions IC programs may reduce post-discharge ED visits, LOS and healthcare costs for thoracic surgery patients, particularly for those in a low care path. As the IC program continues, further research is needed with larger sample sizes to confirm these findings and optimize IC program delivery, especially for more complex surgical patients.